2011
DOI: 10.19030/jabr.v10i3.5921
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Orientation, Distinctive Marketing Competencies And Organizational Performance

Abstract: <span>This study examined the entrepreneurial orientation (EO) of 599 independent businesspeople and compared those with high, medium and low EO along a series of distinctive marketing competency and organizational performance measures. EO is measured using a new multi-item scale that is based on an integrative definition of entrepreneurship. Results indicate that EO is positively and significantly related to distinctive marketing competencies and organizational performance. Demographic profiles of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
148
1
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(164 citation statements)
references
References 0 publications
5
148
1
5
Order By: Relevance
“…Some of the research found that EO has positive effect and significant on organizational performance (Lee, Lim, & Pathak, 2011;Lumpkin & Dess, 1996;Wang, 2008;Wiklund & Shepherd, 2003), however on the other hand, some of them did not find a positive relationship between EO and organizational performance (Li, Zhang, & Chan, 2005;Smart & Conant, 1994), or negative impact on performance (Hart, 1992). The inclusiveness in results about the EO-organizational performance relationship, lead us to examine this relationship.…”
Section: Entrepreneurial Orientation (Eo) and Organizational Performamentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the research found that EO has positive effect and significant on organizational performance (Lee, Lim, & Pathak, 2011;Lumpkin & Dess, 1996;Wang, 2008;Wiklund & Shepherd, 2003), however on the other hand, some of them did not find a positive relationship between EO and organizational performance (Li, Zhang, & Chan, 2005;Smart & Conant, 1994), or negative impact on performance (Hart, 1992). The inclusiveness in results about the EO-organizational performance relationship, lead us to examine this relationship.…”
Section: Entrepreneurial Orientation (Eo) and Organizational Performamentioning
confidence: 99%
“…The relationship between EO and organizational performance has been studied by many writers. However, some of them reported that EO has a positive relationship with organizational performance (Jogaratnam & Tse, 2006;Lee, Lim, & Pathak, 2011), others found an adverse result (Li, Zhang, & Chan, 2005;Smart & Conant, 1994). Therefore, the previous conflicting results require further studies and investigation to explore the reasons behind this conflicting and what mechanism can explain the relationship better to have positive results.…”
Section: Introductionmentioning
confidence: 99%
“…Morgan & Strong [11]; Smart & Conant [12]). There can be several reasons behind these inconsistent and at times contradictory findings.…”
Section: Introductionmentioning
confidence: 99%
“…Firms where operations and procedures are organized by formal rules are less likely to facilitate innovation, as they are more oriented toward realizing processes than goals (Barringer & Bluedorn, 1999). These help us to predict higher EO when the functional diversity of entrepreneurial team is high (Smart & Conant, 1994). Recent publications have reported that the role of diversity in an entrepreneurial team may have positive impacts on performance with the logic of entrepreneurial team diversity (Khan, Breitenecker, Gustafsson, & Schwarz, 2015;.…”
Section: The Influence Of Functional Diversity In An Entrepreneurial mentioning
confidence: 99%